Comparison of series/parallel configuration for a low-T geothermal CHP plant, coupled to thermal networks. (October 2017) - Van Erdeweghe, Sarah; Van Bael, Johan; Laenen, Ben; D'haeseleer, William
Abstract: In this paper, the performance of a low-temperature (130 °C) geothermally-fed combined heat-and-power (CHP) plant coupled to third and fourth generation thermal networks is investigated. The series and parallel CHP configurations are compared based on an exergy analysis. Whether the series or the parallel CHP has the best performance depends on the thermal network requirements. The results are discussed for a wide range of supply (40–110 °C) and return (30–70 °C) temperatures and for three values of the heat demand. The heat-to-electricity conversion is done via an Organic Rankine Cycle (ORC). In general, the parallel configuration is the most appropriate for the connection to high-temperature thermal networks and the series configuration performs better for the connection to low-temperature thermal networks. For a nominal heat demand of 6 MW, the parallel configuration connected to a 80/60 thermal network has an exergetic plant efficiency of 41.25% which is 1.67%-pts higher than for a pure electrical power plant. The corresponding electrical power output is 89% of the pure electrical power plant. The series configuration connected to a 50/30 thermal network has an exergetic efficiency of 42.63%, which is 3.05%-pts higher than for a pure electrical power plant and produces the same electrical power output. An additional important finding is that for isentropic and dry ORC fluids, the use of superheating might increase the electrical power output if the ORC outlet temperature is constrained to a relatively high value. For the investigated brine conditions and R236ea as a working fluid, the use of superheating improves the electrical power output already for ORC outlet temperatures higher than 80 °C in case of a recuperated ORC. For the basic cycle, this is only for ORC outlet temperatures higher than 109 °C. Highlights: We indicate the best configuration for Tsupply in 40–110 °C and Treturn in 30–70 °C. The parallel configuration is optimal for high-T thermal networks. The series configuration is optimal for low-T thermal networks. The studied CHP configurations reach higher η e x than a pure electrical power plant. Superheating improves the ORC power for dry/isentropic fluids at high ORC outlet T.